Ilustrasi Karya Pawel Kuczynski Bertema Anak-Anak (Analisa Relasi Antar Tanda : Metafora-Metonimi-Kontradiksi) - Sarrahdiba, Tyara Umi Yuhanis (LPPM BSI Bandung, 2014)
Abstract - Illustration is visual art that has function to give an explanation of something or a purpose in visual. This day illustration has penetrated into various media such as sketch pictures, graphic, and caricature, with different styles. One of the artist is Pawel Kuczynski who criticize the social problem, economic and political issues with his satire style illustration. One of his works discussed the issue of children. There are similarities between all visual communication style works Pawel Kuczynski. This can be seen from the visual signs and their relationships that used in each illustration. Through this study, the authors will describe 6 illustrations attempting Kuczynski works with the theme of children and dissected using a sign and relationships that exist in order to determine the meaning contained therein. Keywords: Children, Illustration, Pawel Kuczynski, Signs Abstrak - Ilustrasi merupakan seni gambar yang berfungsi untuk memberi penjelasan tentang sesuatu atau suatu maksud secara visual. Perkembangan ilustrasi saat ini telah merambah ke berbagai media seperti sketsa gambar, grafis, dan karikatural, dengan gaya yang berbeda. Salah satunya seorang seniman dari Polandia yaitu Pawel Kuczynski yang mengkritik masalah sosial, ekonomi dan isu politik dengan ilustrasi gaya satirnya. Salah satu karyanya membahas mengenai isu anak-anak. Terdapat kesamaan gaya komunikasi visual diantara semua karya Pawel Kuczynski. Hal ini terlihat dari penggunaan tanda-tanda visual dan relasinya yang digunakan dalam setiap ilustrasi. Melalui penelitian ini, penulis akan memcoba memaparkan 6 ilustrasi karya Kuczynski dengan tema anak-anak dan membedah penggunaan dan relasi tanda yang ada guna mengetahui makna yang terkandung di dalamnya. Kata Kunci: Anak-Anak, Ilustrasi, Pawel Kuczynski, Tanda